Pragmatic non-inferiority Randomised trial Investigating Needle aspiration versus ChEst drain for Secondary Spontaneous Pneumothorax (the PRINCE-SSP study): study protocol for a randomised non-inferiority trial - Nick A Maskell; Edward Carlton; Siobhan Creanor; Ramon Luengo-Fernandez; Heather Cook; Steven Walker; James Connors; Ellie Taylor; Amy McAndrew; Ella Chaudhuri; Pooja Ghorpade; Charlotte Goodwin (BMJ Open)
Introduction Secondary spontaneous pneumothorax (SSP) is a medical emergency where the lung collapses in the presence of underlying chronic lung disease. Current international clinical guidelines advise intercostal drain (ICD) insertion for SSP. However, in a previous small study needle aspiration (NA) has been shown to reduce length of hospital stay (LOHS) and reduce complications. We are evaluating the clinical and cost-effectiveness of an initial NA approach to the management of patients with SSP in the United Kingdom.Methods and analysis The PRINCE-SSP (Pragmatic non-inferiority Randomised trial Investigating Needle aspiration vs ChEst drain for Secondary Spontaneous Pneumothorax) trial is a pragmatic, multicentre, open-label, parallel, two-group, randomised, non-inferiority trial to establish whether NA for SSP is non-inferior in terms of LOHS compared with ICD. We aim to recruit 110 patients from at least 15 UK NHS hospitals, over 18 months. Participants allocated to the intervention (NA) group will have an NA inserted at the presentation. Those allocated to the comparator (usual care) group will have an ICD inserted. Participants are followed up for 30 days. The primary outcome measure is initial LOHS, up to day 30 postrandomisation. Secondary outcomes include (but are not limited to) total LOHS including readmissions, complications, cost-effectiveness and patient-reported quality of life.Ethics and dissemination This trial received Health Research Authority (HRA) approval from Wales Research Ethics Committee seven ethics committee (23/WA/0085). Results will be submitted for publication in a peer-reviewed journal. A plain English summary of the trial results will be prepared and disseminated with the help of our patient advisory group, including via social media, and provided to trial participants via post or email according to their preference.Trial registration number ISRCTN12644940.